2004
DOI: 10.1021/jp048667l
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Thermochemistry of Tin Dibromide Monomers and Dimers. A Computational and Electron Diffraction Study

Abstract: The molecular structure of tin dibromide was investigated by high-level computational methods and gasphase electron diffraction. The structural and vibrational characteristics of both SnBr 2 and Sn 2 Br 4 were determined by computations. To reach an agreement between computed and experimental bond lengths for SnBr 2 , very large bases and correlated methods are needed. For the dimer Sn 2 Br 4 , two low-energy geometries were found, one with C s and the other with C 2V symmetry, the former with somewhat lower e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…1 These structures were calculated at higher computational levels as well and their geometrical parameters are given in Table 2. These two structures are very similar to the ones found stable for tin dichloride and dibromide [5,[11][12][13], perhaps one difference can be mentioned: for the C 2v -symmetry isomer the central four-membered ring puckers towards the terminal iodines, while in the tin dichloride and dibromide dimers this puckering is in the opposite direction; obviously the large size of the iodine atoms being the reason. The terminal bond lengths of the dimer are about 0.02-0.04 Å longer than the corresponding monomer bonds, and the bridging bonds are considerably, about 0.16-0.18 Å , longer than the terminal bonds-as expected.…”
Section: Dimersupporting
confidence: 68%
See 2 more Smart Citations
“…1 These structures were calculated at higher computational levels as well and their geometrical parameters are given in Table 2. These two structures are very similar to the ones found stable for tin dichloride and dibromide [5,[11][12][13], perhaps one difference can be mentioned: for the C 2v -symmetry isomer the central four-membered ring puckers towards the terminal iodines, while in the tin dichloride and dibromide dimers this puckering is in the opposite direction; obviously the large size of the iodine atoms being the reason. The terminal bond lengths of the dimer are about 0.02-0.04 Å longer than the corresponding monomer bonds, and the bridging bonds are considerably, about 0.16-0.18 Å , longer than the terminal bonds-as expected.…”
Section: Dimersupporting
confidence: 68%
“…The density functional calculations consistently gave several hundredths of an angstrom larger bond lengths and also somewhat larger bond angles than the MP2 calculations. We had a similar experience with our calculations of the SnBr 2 structure [12]. Since the MP2 and CCSD(T) computed geometries of the monomer agreed much better with the experimental results than the density functional ones, our discussion is based on these results.…”
Section: Computational Detailsmentioning
confidence: 72%
See 1 more Smart Citation
“…Magdi and her co-workers found structures that were fully consistent with the presence of such lone pairs. Figure 6 demonstrates the models [14,15]. The two structures are of very similar energies, therefore, if they appear in the vapor phase, probably both would appear.…”
Section: Metal Dihalidesmentioning
confidence: 97%
“…Thermodynamic calculations show that, although the geometry of the dimer is very different from the usual D 2h symmetry arrangement of metal dihalide dimers, this difference hardly has any effect on thermodynamic functions of the dimer. Related studies of gaseous tin dichloride [300,301] and dibromide [302] were earlier reported and in addition, Br/I exchange enthalpies in related mixed tin dihalide dimers have also been investigated [303].…”
Section: Issuementioning
confidence: 98%